Use of Schizosaccharomyces pombe and Torulaspora delbrueckii strains in mixed and sequential fermentations to improve red wine sensory quality. (October 2015) - Loira, Iris; Morata, Antonio; Comuzzo, Piergiorgio; Callejo, María Jesús; González, Carmen; Calderón, Fernando; Suárez-Lepe, José Antonio
Abstract: One of the main opportunities in the use of non- Saccharomyces yeasts is its great intraspecific variability in relation to the synthesis of secondary products of fermentation. Thus, mixed or sequential fermentation with non- Saccharomyces can increase the synthesis of certain metabolites that are important for colour stability, such as acetaldehyde and pyruvic acid (vitisin precursors) or vinylphenols (vinylphenolic pyranoanthocyanin precursors). Furthermore, the selection and use of non- Saccharomyces yeast strains with good yields in the production of certain volatile compounds (ethyl lactate, 2, 3-butanediol, 2-phenylethyl acetate), with limited formation of higher alcohols, is a way to improve the aromatic profile of red wine. The main aim of this work was to evaluate the influence of sequential and mixed fermentations with Schizosaccharomyces pombe and Torulaspora delbrueckii strains on red wine's sensory quality. Anthocyanins and aromatic profiles, as well as glycerol and organic acid content, were analysed in the red wines obtained. Results show that, in general, mixed fermentations can promote an increment in polyols synthesis, while sequential fermentations can enhance the herbaceous aroma. Moreover, the use of T. delbrueckii in mixed fermentations allowed an increase to the fruity character of red wine. The use of S. pombe in sequential fermentations increased the stability of the colouring matter by favouring vitisins and vinylphenolic pyranoanthocyanin formation. Highlights: Use of Schizosaccharomyces pombe in sequential fermentation allows increasing the contents of vitisins, especially A type. Use of Torulaspora delbrueckii in mixed fermentation allows a potential increase of fruity aromas in the wine. Mixed fermentations with non- Saccharomyces yeasts may increase polyol content. 3-ethoxy-1-propanol was found as a compound linked to T. delbrueckii' s metabolism. Use of S. pombe in mixed or sequential fermentations allows tempering of its characteristic high acetic acid synthesis.